Falls and outcomes amongst old people in rural dwellings (2009)
Background: Falls are the leading cause of injury deaths among people 65 years and older. This study gives an insight into the prevalence of falls among older people and how they occur in a rural setting in Nigeria. Methods: A community based survey of 210 consenting old people aged 65 years and above selected using a multi-stage sampling technique was done. Study instrument was a semi-structured interviewer administered questionnaire and visual acuity was tested using Snellens chart. Results: Incidence of falls was 21.4%. Of those who had falls, 86.7% were walking while 11.1% were either sitting or running when it occurred. The nature of the fall was tripping in 44.4%, slipping in 35.6% and hitting an object in 17.8% of cases. Consequences of falls included pain 48.9%, bruises 22.2%, lacerations 13.3% and fractures 11.1%. Females had more falls than males; 23.8% vs 19.0%, p = 0.40. Major injuries resulting from falls also occurred more frequently amongst females than males; 30.7% vs. 15.0%, p = 0.3. History of diabetes and alcohol use increased the odds of falling (OR 4.1, 95% CI 1.0 – 16.0; OR 2.2, 95% CI 1.0 – 4.6 respectively). Being in a monogamous marriage and having normal sight were protective of having falls (OR 0.4, 95% CI 0.2 – 0.9; OR 0.4, 95% CI 0.2 – 0.9 respectively). Conclusion: Falls often occur from tripping and slipping while females are more likely to have major injuries. Risk factors for falls were alcohol use and diabetes while having normal sight and being monogamous were protective. Prevention should aim at a life course approach to addressing these intrinsic and extrinsic factors.